2016
DOI: 10.1002/ange.201510497
|View full text |Cite
|
Sign up to set email alerts
|

Lewis‐Säure‐unterstützte metallkatalysierte Kreuzkupplung: Alkylierung von Arylmethylethern unter C‐O‐Bindungsspaltung ohne β‐Hydrideliminierung

Abstract: Diverse Arylmethylether kçnnen durch Trialkylaluminiumverbindungen mittels einer Alkylierung unter C-O-Bindungsspaltung in wertvolle Produkte überführt werden, wobei die bislang limitierenden b-Hydrideliminierungen vermieden werden. Basierend auf der Vielfalt natürlich vorhandener oder leicht zugänglicher Anisolderivate ermçglicht die neue Nickel-katalysierte dealkoxylierende Alkylierung orthogonale Synthesestrategien, die zunächst die dirigierenden und/ oder aktivierenden Eigenschaften von Methoxysubstituente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…Thus, AlMe 3 lowers that activation barrier by approximately 5 kcal mol −1 , which is in notable agreement with the experimental values. Lowering of the activation barrier for oxidative addition to Ni by coordinated Lewis acids has been noted by previous computational studies ,. After oxidative addition and transmetalation, the Ni II −Me species D (corresponding to 2‐R ) is afforded.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, AlMe 3 lowers that activation barrier by approximately 5 kcal mol −1 , which is in notable agreement with the experimental values. Lowering of the activation barrier for oxidative addition to Ni by coordinated Lewis acids has been noted by previous computational studies ,. After oxidative addition and transmetalation, the Ni II −Me species D (corresponding to 2‐R ) is afforded.…”
Section: Methodssupporting
confidence: 53%
“…In the case of boron‐based reagents, both boronic acid and triethyl borane are proposed to interact with the phenolic aryl oxygen. Similarly, Al and Mg cations were shown by computation to coordinate to the ether oxygen and facilitate the oxidative addition step ,. Lewis acid effects have also been invoked for the cleavage of vinylic C−O and aryl–halide bonds…”
Section: Methodsmentioning
confidence: 99%
“…[10] Amongthem aryl alkyl ethers (ArOR) appear particularly attractive, [11] featuring easya ccessibility,s tructurald iversity, low cost, and ah igh atom efficiency.I n1 979, Wenkert et al reportedt he first cross-coupling reactiono fa ne ther with aG rignard reagent in the presence of aN ic atalyst. [12] In recent decades, several groups,i ncluding ours, have developed various types of etheric cross-coupling reactions, including Kumada-Tamao-Corriu, [13] Suzuki-Miyaura, [14] Negishi, [15] and other reactions. [16] In 2014 and 2015, Rueping et al reported aN i-catalyzed alkylation of aryl or alkenyl ethers with TMS-CH 2 Li (TMS = trimethylsilyl), in which the C(sp 2 )ÀOb ond cleavage occurred in the absence of al igand.…”
Section: Resultsmentioning
confidence: 99%
“…Rueping has expanded on these findings to develop a Ni-catalysed alkylation protocol for aryl ethers using trialkylaluminium reagents as the nucleophilic coupling partner. 34 Surprisingly, no undesirable β-hydride elimination is observed under the optimised conditions, and whilst a diverse range of trialkylaluminium nucleophiles could be employed, this method is not compatible with cyano, ester, and amide functional groups. Furthermore, this reaction only works using the bidentate phosphine ligand, dcype [1,2-bis(cyclohexylphosphino)-ethane], and still requires harsh conditions (100–120 °C, 12–72 hours) in combination with electron-deficient or π-extended aryl ethers.…”
Section: Lewis Acid Assisted C–o Bond Cleavagementioning
confidence: 99%